2020
DOI: 10.1101/2020.11.17.387043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotational dynamics in motor cortex are consistent with a feedback controller

Abstract: SummaryRecent studies hypothesize that motor cortical (MC) dynamics are generated largely through its recurrent connections based on observations that MC activity exhibits rotational structure. However, behavioural and neurophysiological studies suggest that MC behaves like a feedback controller where continuous sensory feedback and interactions with other brain areas contribute substantially to MC processing. We investigated these apparently conflicting theories by building recurrent neural networks that cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…The engineering term for this is rotational dynamics. Such activity has been found in primate motor cortex and it is produced by artificial neural networks trained to perform similar tasks; for recent results and review see ( Kalidindi et al, 2020 ).…”
Section: Good-enough Programs Vs Optimal Control Of Synergiesmentioning
confidence: 97%
“…The engineering term for this is rotational dynamics. Such activity has been found in primate motor cortex and it is produced by artificial neural networks trained to perform similar tasks; for recent results and review see ( Kalidindi et al, 2020 ).…”
Section: Good-enough Programs Vs Optimal Control Of Synergiesmentioning
confidence: 97%
“…Primary motor cortex (M1) plays an important role in generating goal-directed corrections during motor actions. M1 receives rich sensory inputs from many brain regions involved in proprioceptive and visual processing including the parietal and frontal cortices (Jones et al, 1978; Zarzecki and Strick, 1978; Crammond and Kalaska, 1989; Porter and Lemon, 1993; Buneo et al, 2002; Pesaran et al, 2006; McGuire and Sabes, 2011; Bremner and Andersen, 2012; Dea et al, 2016; Omrani et al, 2016; Gamberini et al, 2017; Piserchia et al, 2017; Kalidindi et al, 2020; Takei et al, 2021), as well as input from cerebellum (Conrad et al, 1975; Vilis et al, 1976; Strick, 1983; Guo et al, 2020; Sauerbrei et al, 2020). M1 rapidly responds to proprioceptive feedback of the limb within ∼20-40ms of an applied mechanical load (Evarts and Tanji, 1976; Wolpaw, 1980; Lemon, 1981a; Suminski et al, 2009; Pruszynski et al, 2011, 2014; Omrani et al, 2014; Heming et al, 2019) and to visual feedback of the limb and goal within ∼70ms (Georgopoulos et al, 1983; Cisek and Kalaska, 2005; Ames et al, 2014; Stavisky et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our model consistently underestimated the changes in trial-averaged activity observed during VR adaptation, despite closely matching the small covariance changes (Figure 2,4). This is to be expected, as the model only captures changes due to the motor adaptation process itself, whereas the actual neural activity contains signals related to other processes such as impulsivity/engagement [Cowley et al, 2020, Hennig et al, 2021 and feedback processing [Omrani et al, 2016, Stavisky et al, 2017, Kalidindi et al, 2020, Perich et al, 2020, Cross et al, 2021. In fact, the experimentally observed neural activity changes between the early and late trials of control reaching sessions with no perturbation were almost as large as the changes during adaptation in our model (Figure 2C black dots).…”
Section: Discussionmentioning
confidence: 99%